Evidence for involvement of both IKCa and SKCa channels in hyperpolarizing responses of the rat middle cerebral artery. - McNeish, A; Sandow, S; Neylon, C; Chen, M; Dora, K; Garland, C (2006)
BACKGROUND AND PURPOSE: Endothelium-derived hyperpolarizing factor responses in the rat middle cerebral artery are blocked by inhibiting IKCa channels alone, contrasting with peripheral vessels where block of both IKCa and SKCa is required. As the contribution of IKCa and SKCa to endothelium-dependent hyperpolarization differs in peripheral arteries, depending on the level of arterial constriction, we investigated the possibility that SKCa might contribute to equivalent hyperpolarization in cerebral arteries under certain conditions. METHODS: Rat middle cerebral arteries (approximately 175 microm) were mounted in a wire myograph. The effect of KCa channel blockers on endothelium-dependent responses to the protease-activated receptor 2 agonist, SLIGRL (20 micromol/L), were then assessed as simultaneous changes in tension and membrane potential. These data were correlated with the distribution of arterial KCa channels revealed with immunohistochemistry. RESULTS: SLIGRL hyperpolarized and relaxed cerebral arteries undergoing variable levels of stretch-induced tone. The relaxation was unaffected by specific inhibitors of IKCa (TRAM-34, 1 micromol/L) or SKCa (apamin, 50 nmol/L) alone or in combination. In contrast, the associated smooth-muscle hyperpolarization was inhibited, but only with these blockers in combination. Blocking nitric oxide synthase (NOS) or guanylyl cyclase evoked smooth-muscle depolarization and constriction, with both hyperpolarization and relaxation to SLIGRL being abolished by TRAM-34 alone, whereas apamin had no effect. Immunolabeling showed SKCa and IKCa within the endothelium. CONCLUSIONS: In the absence of NO, IKCa underpins endothelium-dependent hyperpolarization and relaxation in cerebral arteries. However, when NOS is active SKCa contributes to hyperpolarization, whatever the extent of background contraction. These changes may have relevance in vascular disease states where NO release is compromised and when the levels of SKCa expression may be altered.